Design and Synthesis of Surface Acoustic Wave Ladder-Type Filter - Tan Bee Chin, Agnes (2017)
There are three kinds of Surface Acoustic Wave (SAW) filter design which are the Interdigitated Interdigital Transducer (IIDT) type design, Double Mode SAW (DMS) type design and ladder-type design. However, this study will focus on the SAW ladder-type filter as filter synthesis approach is applied to obtain a ladder filter network. A SAW ladder-type filter consists of SAW resonators connecting in series and shunt to obtain a bandpass filter response. This project introduces a technique to synthesize SAW ladder-type filter from generalized Chebyshev filtering function. The SAW filter network is designed based on the resonators’ model and mapped with the synthesized network to obtain the lumped-element values of SAW ladder-type filter. 1-stage and 2-stage SAW ladder-type filter networks centered at 2.14GHz and 60 MHz bandwidth (Band 1) are simulated in ADS after obtaining the elements’ values using generalized Chebyshev filter synthesis and mapping approach. This is first time ever reported the exact synthesis approach of SAW ladder-type filter network based on proposed generalized Chebyshev filtering function with prescribed transfer characteristic. The simulated response shows excellent agreement with the commercial device performance where Band 1 operating frequency is demonstrated.